Immunocytochemical analysis of HLA class II (DR) antigens in liver disease in man. Issue 8 (August 1987) - Barbatis, C; Kelly, P; Greveson, J; Heryet, A; McGee, J O
Abstract : The in situ distribution of the major histocompatibility (HLA) class II (DR) antigens was studied in 113 liver biopsy specimens and five livers obtained at necropsy, using monoclonal antibody CR3/43. In 20 normal livers HLA-DR antigens were not detected in bile duct epithelium, hepatocytes, or portal vein endothelium. Normal arteriolar, sinusoidal and central venous endothelium often expressed HLA-DR. Kupffer cells always expressed these antigens. HLA-DR positive spindle cells were identified in the connective tissue of portal tracts, large hepatic veins, and liver capsule: most shared antigens common to all leucocytes and reacted with the histiocytic maker EBM11. Bile duct epithelium expresses HLA-DR in primary biliary cirrhosis, large duct obstruction, and drug induced cholestasis, indicating that HLA-DR positive spindle cells are phenotypically similar to histiocytes.